(untitled) (Medical Forum Monthly, 2024)
Objectives: To study the Prevalence of hysterectomy in women in Sialkot. Study Design: Observational / descriptive study. Place and Duration of Study: This study was conducted at the Department of Obstetrics and Gynecology, Idris Teaching Hospital Sialkot and Islam Teaching Hospital Sialkot from January 2014 to August 2016. Materials and Methods: Seventy five women with hysterectomy were included in this retrospective study during January 2014 to August 2016 at Idris Teaching Hospital Sialkot and Islam Teaching Hospital Sialkot. Performa was designed to record age, area; type of hysterectomy (vaginal or abdominal) and indications of hysterectomy. The well informed consent was taken prior to operation from every patient. Permission of ethical committee was also taken. The results were analyzed on SPSS version 10. Results: The prevalence of hysterectomy was maximum (41.3%) n=31 at the age of 38 – 47 years and minimum (9.3%) n=07 at the age of 18-27 years. The women from rural area had almost double prevalence (65.3%) n= 49 as compared to women of urban area (34.7%) n=26. The prevalence of abdominal hysterectomy in women was much higher (81.3%) n= 61 as compared to vaginal hysterectomy (18.7%) n= 14. In case of indications of hysterectomy in women was maximum in dysfunctional uterine bleeding (44%) n= 33 as compared to cancer of uterus and ovaries and genital prolapsed (13.3%) n= 10 and (14.7%) n= 11 respectively.